Alternativas de inclusión social para el movimiento hip hop de los jóvenes del barrio Monserrath de Otavalo - Cachimuel, Sumay Y. (2018)
The Hip Hop culture originated in the late 70 in the midst of marginal social events in the United States where its main actors were African-American people victims of discrimination, racism, and police abuse. Hip Hop is made up of four elements that are the Dj, Graffiti, Break dance, Mc, this last component is in charge of writing the letters of rap where the thought, ideology and proposals of change by the young people are announced.